Estudio de factibilidad para creación de una empresa procesadora y comercializadora de saquitos filtrantes de café en la ciudad de Cali (2014)
The evolutionary trend worldwide is making that many staple products, like coffee, is modifying in the way that they are being presented. An innovative approach causes an original idea face new challenges, due to the criticism that consumers have acquired, making them a more demanding consumers when it comes to choosing a product that not only has good price, and that is also innovative, that has a primary objective to satisfy the daily needs for different consumers. This feasibility study aimed to develop an analysis that would allow us to determine the viability and profitability of creating a company that processes and sells filter bags of coffee in Cali, Colombia. To achieve this objective, research was conducted in different areas such as cultural, social, political, economic and environmental surroundings. Similarly, different types of marketing, financial, administrative, and technical studies were performed in the area where the business idea was developed. This study would allow the team to know people’s acceptance of the filter bags of coffee and how attractive and rewarding can be for the consumers. The results obtained were instrumental in shaping the company, serving as a framework for research that would provide clear and precise information to people who might be interested in this subject. This research that not only provides ideas, but also solutions to a problem experienced in the region, such as the lack of new job opportunities. The goal of COFFEECOL S.A.S. is to offer an innovative and practical product, as well as to give consumers an alternative by providing high quality coffee that is 100% organic, and that can be prepared in a minimal amount of time.